The Truncated q-Bernstein Polynomials in the Case q>1. (5th March 2014) - Turan, Mehmet
Abstract : The truncated q -Bernstein polynomials B n, m, q f ; x, n ∈ ℕ, and  m ∈ ℕ 0 emerge naturally when the q -Bernstein polynomials of functions vanishing in some neighbourhood of 0 are considered. In this paper, the convergence of the truncated q -polynomials on 0, 1 is studied. To support the theoretical results, some numerical examples are provided.